2014
DOI: 10.12669/pjms.311.6524
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP in FTO gene, rs9939609, with metabolic syndrome at a tertiary care unit of Karachi, Pakistan

Abstract: Objective:To determine the association of SNP in FTO gene, rs9939609, with Metabolic Syndrome (MS) in type 2 diabetic subjects at a tertiary care unit of Karachi, Pakistan.Methods:We genotyped FTO rs9939609 SNP in 296 patients with type 2 diabetes from the Out Patient Department (OPD) of Baqai Institute of Diabetology and Endocrinology (BIDE). MS was defined on the basis of International Diabetes Federation (IDF) and National Cholesterol Education program (NCEP) criterion. Association between the rs9939609 SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The FTO rs9939609 and rs1421085 variants were detected using amplification-refractory mutation system (ARMS) polymerase chain reaction (PCR). Detection of rs9939609 was performed using a previously published primer sets (Fawwad et al, 2015) while detection of rs1421085 was done using a novel primer sets, designed using Primer1 (Collins & Ke, 2012) and BioEdit Ò Sequence Alignment Editor (Ibis Bioscience, Carlsbed, CA, USA). Lists of outer and inner primers for ARMS-PCR is described in Table S1.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…The FTO rs9939609 and rs1421085 variants were detected using amplification-refractory mutation system (ARMS) polymerase chain reaction (PCR). Detection of rs9939609 was performed using a previously published primer sets (Fawwad et al, 2015) while detection of rs1421085 was done using a novel primer sets, designed using Primer1 (Collins & Ke, 2012) and BioEdit Ò Sequence Alignment Editor (Ibis Bioscience, Carlsbed, CA, USA). Lists of outer and inner primers for ARMS-PCR is described in Table S1.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Subsequently, further studies demonstrated that the allele A of FTO rs9939609 is related to both a higher body mass index and body circumferences [ 21 , 22 ], and, among different ethnicities, also Italian population demonstrated the same results [ 23 ]. Furthermore, this SNP is included among the genetic etiological factors in the development of both metabolic syndrome and Type-2 diabetes [ 24 , 25 ], and allele A was also associated with a higher fat and lean mass [ 26 , 27 ]. In a PREDIMED substudy, it was observed that homozygous subjects for A allele had the highest baseline body weight, but also the lowest body weight gain after 3 years of Mediterranean-style intervention, compared to TT genotype.…”
Section: Introductionmentioning
confidence: 99%
“…The FTO rs9939609 and rs1421085 variants were detected using amplification-refractory mutation system (ARMS) polymerase chain reaction (PCR). Detection of rs9939609 was performed using a previously published primer sets (Fawwad et al, 2015) while detection of rs1421085 was done using a novel primer sets, designed using Primer1 (Collins & Ke, 2012) and BioEdit® Sequence Alignment Editor (Ibis Bioscience, Carlsbed, CA, USA). Lists of outer and inner primers for ARMS-PCR is described in Supplementary Table S1.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Among the significant obesity genetic risk factors, the common single nucleotide polymorphisms (SNPs) rs9939609 and rs1421085 in the fat mass and obesity-associated (FTO) gene have been consistently reported to be associated with obesity in distinct populations (Chang et al, 2008;Cha et al, 2008;Fawwad et al, 2015;Babenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%